The Impact of Sociodemographic Variables on Risk Factors Associated with Ischaemic Stroke Patients by Age Group - Loh, Hong Chuan; Kwan, Jia Ni; Ramlee, Siti Nur Liyana; Looi, Irene (Journal Of Cardiovascular, Neurovascular & Stroke, 2022)
This study aims to identify the relevant risk factors based on different sociodemographic backgrounds among ischaemic stroke patients in relation to age. We included all adult ischaemic stroke patients from 1st January 2013 to 31st December 2019 who presented to Hospital Seberang Jaya. The study utilized data that were collected from medical records and were presented with descriptive and inferential statistics.